Prostate-specific antigen at or before age 50 as a predictor of advanced prostate cancer diagnosed up to 25 years later: a case-control study. - Ulmert, D; Cronin, A; Björk, T; O'Brien, M; Scardino, P; Eastham, J; Becker, C; Berglund, G; Vickers, A; Lilja, H (BioMed Central, 2008)
BACKGROUND: Based on a large, representative unscreened cohort from Malmö, Sweden, we have recently reported that a single prostate-specific antigen (PSA) measurement at or before age 50 is a strong predictor of prostate cancer occurring up to 25 years subsequently. We aimed to determine whether this association holds for advanced cancers, defined as clinical stage T3 or higher, or skeletal metastasis at the time of the cancer diagnosis. METHODS: In 1974-1986 blood samples were obtained from a cohort of 21,277 men aged up to 50. Through 1999, 498 men were diagnosed with prostate cancer, and of these 161 had locally advanced or metastatic prostate cancers. Three controls, matched for age and date of venipuncture, were selected for each case. Conditional logistic regression was used to test associations between molecular markers and advanced cancer. RESULTS: Median time from venipuncture to diagnosis was 17 years. Levels of all PSA forms and hK2 were associated with case status. Total PSA was a strong and statistically significant predictor of subsequent advanced cancer (area under the curve 0.791; p < 0.0005). Two-thirds of the advanced cancer cases occurred in men with the top 20% of PSA levels (0.9 ng/ml or higher). CONCLUSION: A single PSA test taken at or before age 50 is a very strong predictor of advanced prostate cancer diagnosed up to 25 years later. This suggests the possibility of using an early PSA test to risk-stratify patients so that men at highest risk are the focus of the most intensive screening efforts.